Improving properties of silicone rubber composites using macromolecular silane coupling agent (MMSCA). Issue 19 (2nd February 2016) - Mei, Honggang; Chen, Guowen; Zhu, Qingzeng; Dong, Peng; Zhao, Dannan; Ahmed Raza, Waqas
ABSTRACT: Two types of vinyl silicone oil (VSO), allyl‐capped hyperbranched polycarbosilane (HBP), and triethoxysilane (TES) were employed to synthesize macromolecular silane coupling agent (MMSCA) by hydrosilylation. VSOs, HBP, and the hydrosilylated products were used as crosslinker, respectively, to improve weak mechanical properties of silicone rubber (SR). Structures of the crosslinkers were studied by gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FTIR), and nuclear magnetic resonance (NMR). Crosslinking density test and scanning electron microscope (SEM) observation showed an increased interaction between silicone rubber and fumed silica by the use of MMSCA. Mechanical properties of the resulted composites using MMSCAs were increased to varying degrees compared with those possessing crosslinkers without ethoxy group. MMSCAs were effective for further property enhancements of composites. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43415. Abstract :